Body composition and the quality of life estimated by the General Health Questionnaire by David Goldberg (GHQ-12) in women aged 55-60 years - Jakubiec, Dorota; Jarnut, Weronika; Jonak, Wiesława; Chromik, Krystyna; Sobiech, Krzysztof A. (Menopause Review/Przegląd Menopauzalny, 2012)
Aim of the study: Evaluation of differences in subjective estimation of quality of life in women aged 55-60 corresponds with differences in body composition of these women. Material and methods: This study was carried out on 32 women aged 55-60 years (56.5 ±4.9), in which the biometric indexes were measured such as BMI and adipose tissue distribution WHR. According to obtained results, patients were divided into two groups: group A (n = 16) – patients with the “pear” type of the distribution of adipose tissue in the lower body zone (WHR 0.74 ±0.12), and group B (n = 16) with the “apple” distribution of adipose tissue in the abdominal body zone (WHR 0.93 ±0.14). The quality of life was estimated by the General Health Questionnaire by David Goldberg (GHQ-12 Goldberg), with cultural adaptation. Results: The research proved that the WHR index, BF index of the total adipose tissue content (expressed by kg and %) as well as the fat-free mass of body (FFM; expressed in %) in group B were higher and statistically significant than in group A, inversely to the age and BMI index differences, which were not statistically significant. The results obtained by the General Health Questionnaire GHQ-12 in particular groups were correlated by a Person correlation coefficient to the body composition compounds WHR, BF (kg), BF (%), FFM (%), which values in both investigated groups were statistically significantly different. A positive correlation between the body composition and the quality of life in women included in group A (BMI 25) this correlation was negative, so it may be assumed that women included in group A have higher quality of life than women included in group B. The physical distress was proportional to the percentage of adipose tissue and inversely proportional to the percentage of the FFM of body. It’s worth noting that even statistically non-significant differences in the BMI index may affect the subjective assessment of the quality of life.